(untitled) (Architecture Image Studies, 2026)
This study investigates the role of design technology in bridging the gap between conceptual ideas and practical implementation, with a focus on fostering a creative digital future. Technological advancements have significantly influenced design processes, providing tools that enhance efficiency, reduce time and costs, and improve comfort while maintaining quality, safety, and budget requirements. The study employed a descriptive developmental approach to explore the reality and expected levels of technology use in design among professionals in graphic, architectural, and engineering design. A total of (384) participants were selected randomly, and data were collected through a structured questionnaire divided into three dimensions: Design Technology, Concept-to-Execution Gap, and Digital Future and Creativity. The validity of the instrument was confirmed by expert review and Pearson correlation analysis, while reliability was verified using Cronbach’s alpha. Results revealed a significant gap between the actual use of technology and the expected level, highlighting the need for greater integration of digital tools in design practice. The study also found a high-level concept-to-execution gap, emphasizing that technology serves as a crucial bridge between creative vision and project realization. Furthermore, participants recognized the importance of digital transformation and technology-driven creativity in shaping the future of design, underscoring the necessity of incorporating technological and digital creativity concepts into educational curricula to prepare innovative designers for the evolving professional landscape.